Alternative Database Structures for Prosopographical Research. Issue 1 (October 2021) - Baillie, James
Abstract : As digital prosopography has developed as a discipline in historical research over the last three decades, and as changes in technology have provided more options for its underlying systems, the potential scope of the field has expanded likewise. This expansion in both what can be done and how it can be done creates new questions of how to select data models and technical infrastructure, and what the implications of those models are for different use cases and forms of analysis. This article discusses current prosopographical systems, largely built with relational databases using the factoid model, and suggests use cases for alternatives and when and why these may be used. In particular, it argues that encoding secondary historical reasoning within a dataset to create databases of single, coherent source readings can be important to facilitate analyses that would face difficulties when applied factoid data. In this discussion, a number of novel distinctions are drawn between purposes and models for prosopographical projects as a suggestion towards a clearer framing of future discussions in this area.